Applying local epidemiological data to national policy - the case study of the epidemiology of wrist and hand injury in Jerusalem - Moran Bodas; Adi Givon; Israeli Trauma Group; Kobi Peleg (BMC, 2019)
Abstract Recently, Luria et al. (2019) published a paper in The Israeli Journal for Health Policy Research describing the epidemiology of wrist and hand injuries in two hospitals in Jerusalem. In this important paper, the authors were able to identify two subpopulations at higher than average risk for such injuries. It should be noted that local epidemiological findings could differ from findings for regional, national and international settings. Therefore, it is important to explore the extent to which these findings can be further generalized to other contexts, especially when considering health policy changes. In this commentary, we explore this notion by comparing the results of the Jerusalem Study to those obtained from the Israel National Trauma Registry for the same period. The findings suggest that extrapolating the local findings to the national level should be done cautiously, in light of various differences that were observed.